Genome‐wide association study of café‐au‐lait macule number in neurofibromatosis type 1. Issue 10 (31st August 2020) - Sung, Heejong; Hyland, Paula L.; Pemov, Alexander; Sabourin, Jeremy A.; Baldwin, Andrea M.; Bass, Sara; Teshome, Kedest; Luo, Wen; ,; Widemann, Brigitte C.; Stewart, Douglas R.; Wilson, Alexander F.
Abstract: Background: Neurofibromatosis type 1 (NF1) is a tumor‐predisposition disorder that arises due to pathogenic variants in tumor suppressor NF1 . NF1 has variable expressivity that may be due, at least in part, from heritable elements such as modifier genes; however, few genetic modifiers have been identified to date. Methods: In this study, we performed a genome‐wide association analysis of the number of café‐au‐lait macules (CALM) that are considered a tumor‐like trait as a clinical phenotype modifying NF1. Results: A borderline genome‐wide significant association was identified in the discovery cohort (CALM1, N  = 112) between CALM number and rs12190451 (and rs3799603, r 2  = 1.0; p  = 7.4 × 10 −8 ) in the intronic region of RPS6KA2 . Although, this association was not replicated in the second cohort (CALM2, N  = 59) and a meta‐analysis did not show significantly associated variants in this region, a significant corroboration score (0.72) was obtained for the RPS6KA2 signal in the discovery cohort (CALM1) using Complementary Pairs Stability Selection for Genome‐Wide Association Studies (ComPaSS‐GWAS) analysis, suggesting that the lack of replication may be due to heterogeneity of the cohorts rather than type I error. Conclusion: rs12190451 is located in a melanocyte‐specific enhancer and may influence RPS6KA2 expression in melanocytes—warranting further functional studies. Abstract : In this study, we performed a genome‐wide association analysis of the number of café‐au‐lait macules (CALM) that are considered a tumor‐like trait as a clinical phenotype modifying neurofibromatosis type 1. A borderline genome‐wide significant association was identified in the discovery cohort (CALM1, N  = 112) between CALM number and rs12190451 ( p  = 7.4 × 10–8) in the intronic region of RPS6KA2. rs12190451 is located in a melanocyte‐specific enhancer and may influence expression of RPS6KA2, a biologically compelling candidate as a NF1 genetic modifier, since the protein is phosphorylated and activated by RAS‐MAPK pathway kinases ERK1/2 that act downstream of RAS and neurofibromin.